STUDI AWAL PERMEABILITAS DAN KUAT TEKAN BETON BERPORI RAMAH LINGKUNGAN DENGAN PEMANFAATAN LIMBAH INDUSTRI - Khairunnisa, Hanyta; Suhaimi; Fadhil, Ammar; Kurnia, RDI (Jurnal Teknik Sipil dan Arsitektur, 2026)
The increasing generation of industrial waste and the growing demand for sustainable construction materials have driven the development of pervious concrete as an environmentally friendly pavement material. Pervious concrete possesses high drainage capability, effectively reducing surface runoff and enhancing groundwater infiltration. This study evaluates the effect of High-Density Polyethylene (HDPE) waste as a partial replacement for coarse aggregate on the compressive strength, density, porosity, and permeability of pervious concrete using split and gravel aggregates at a water–cement ratio (w/c) of 0.40. HDPE was incorporated at 0%, 5%, 10%, and 15% by weight of coarse aggregate, and testing was conducted at 28 days. The results show that compressive strength decreased from 16.75 MPa to 10.32 MPa for gravel and from 18.92 MPa to 15.41 MPa for split aggregate. Density declined from approximately 2100 kg/m³ to about 1850 kg/m³ with increasing HDPE content. Conversely, porosity increased from 30–32% to 37–38%, while permeability rose from approximately 29–35 mm/s to 44–46 mm/s. A strong correlation (R² > 0.80) was found between porosity and permeability, indicating that hydraulic performance is predominantly governed by the interconnected pore structure induced by HDPE modification. Overall, a 5% HDPE substitution achieved the best balance between structural strength and drainage performance without significant strength loss, supporting the implementation of green infrastructure principles in sustainable pavement systems, whereas HDPE contents above 10% were mechanically inefficient.